PYLORIC ATRESIA ASSOCIATED WITH EPIDERMOLYSIS BULLOSA- A CASE REPORT - Alisha Saleem; Khan , Ashar Masood; Ahmed , Mushtaq (Journal of Ayub Medical College Abbottabad, 2024)
Pyloric atresia is a rare congenital condition marked by obstruction of the gastric outflow because the pylorus is absent or severely narrowed. Blistering and fragility of the skin and mucous membranes are symptoms of the hereditary condition epidermolysis bullosa (EB). It is highly uncommon for pyloric atresia and epidermolysis bullosa to co-occur, and this presents substantial diagnostic and treatment difficulties. We describe a case of a newborn who was born with pyloric atresia and epidermolysis bullosa, focusing on the clinical presentation, the diagnostic procedure, and the surgical therapy. The complex interactions between these two dissimilar illnesses highlight the value of a multidisciplinary approach combining neonatologists, dermatologists, and paediatric surgeons for precise diagnosis and thorough care. By sharing this case report, we hope to add to the limited literature on this particular set of congenital defects and highlight the importance of increased clinical awareness and team-based treatment approaches when dealing with cases this complicated.